Pengaruh Ukuran Perusahaan dan Profitabilitas Terhadap Struktur Modal Pada Perusahaan Makanan dan Minuman di Indonesia - Dyan Nur Aulia (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe research method used in this study is a quantitative method, the independent variables used in this study consist of company size, and profitability while the dependent variable is the capital structure. The population in this study are food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) listed on the Indonesia Stock Exchange 2013-2017 period. Sample selection through purposive sampling method. There are 9 (nine) companies that have criteria as research samples, so that the research data totaled 45 data. Data collection techniques used are document review, the data analyzed are annual financial reports (annual report), previous research journals and other literature relating to research problems. Data processing and analysis techniques include financial management analysis, multiple linear regression analysis, classic assumption test, hypothesis test, coefficient of determination test and coefficient of determination test. The results showed that the company size partially had no effect and no significant effect on capital structure, and profitability was partially positive and significant effect on capital structure. While simultaneously the size of the company, and profitability affect the capital structure.